Coenzyme Q10 Analogues: Benefits and Challenges for Therapeutics - Juan M. Suárez-Rivero; Carmen J. Pastor-Maldonado; Suleva Povea-Cabello; Mónica Álvarez-Córdoba; Irene Villalón-García; Manuel Munuera-Cabeza; Alejandra Suárez-Carrillo; Marta Talaverón-Rey; José A. Sánchez-Alcázar (MDPI AG, 2021)
Coenzyme Q10 (CoQ10 or ubiquinone) is a mobile proton and electron carrier of the mitochondrial respiratory chain with antioxidant properties widely used as an antiaging health supplement and to relieve the symptoms of many pathological conditions associated with mitochondrial dysfunction. Even though the hegemony of CoQ10 in the context of antioxidant-based treatments is undeniable, the future primacy of this quinone is hindered by the promising features of its numerous analogues. Despite the unimpeachable performance of CoQ10 therapies, problems associated with their administration and intraorganismal delivery has led clinicians and scientists to search for alternative derivative molecules. Over the past few years, a wide variety of CoQ10 analogues with improved properties have been developed. These analogues conserve the antioxidant features of CoQ10 but present upgraded characteristics such as water solubility or enhanced mitochondrial accumulation. Moreover, recent studies have proven that some of these analogues might even outperform CoQ10 in the treatment of certain specific diseases. The aim of this review is to provide detailed information about these Coenzyme Q10 analogues, as well as their functionality and medical applications.